Peranan Fakulti Kejuteraan Di Universiti Teknologi Malaysia Dalam Mengeluarkan Graduan Bagi Memenuhi Keperluan Tenaga Kerja Industri - Abdullah, Mohd Fauzy (1994)
The main purpose of the study is to explore the role of Faculties Engineering in Universiti Teknologi Malaysia (UTM) in developing the Human Resources Management in line with the needs of the development of Sciece and Technology. The study emphasize on the number of students trained by the University for the last 20 years and the technical know-how gained by student from the subject that have been taught. The research is presented descriptively where information are gathered through secondary sources, questionnaires and interviews with student and the University's staff. The population of the study include the final year Diploma students and the undergraduate student of the Engineering Faculties where by 60 student are chosen randomly using stratified random sampling technique. Subsequently a number of University's officers are also chosen to give additional information. Feedback given by 50 industrial companies also provide additional information regarding the graduates. Overall, the study has found that the Engineering Faculties in UTM is the major contributor in producing professional and semi-professional graduates in Engineering into the labour market. This is obvious as UTM is the sole University in the country that is engineering-based. In the last 20 years, UTM has produced 3,808 undergraduates and 10,880 diploma holders. This is comparatively high compared to other universities that offer the same courses.